3,4-Diaminopyridine in the treatment of congenital (hereditary) myasthenia. - Palace, J; Wiles, C; Newsom-Davis, J (1991)
Congenital or hereditary myasthenia describes a heterogeneous group of disorders in which the immune system is not implicated. Treatment has previously depended on anticholinesterase medication. The effectiveness of 3,4-diaminopyridine (3,4-DAP), a preparation that enhances acetylcholine release from motor nerve terminals, has been evaluated using a series of standardised strength measures. Sixteen patients (aged seven to 47 years) were studied in an open prospective trial, and four of them in a double blind crossover trial; existing anticholinesterase medication was continued. For the group as a whole, there was a highly significant increase in muscle strength (p less than 0.001; n = 16). In individual paired comparisons, 13 out of 16 showed significant improvement in the open trial and four out of four in the blind crossover trial. In conclusion, 3,4-DAP, either alone or combined with anticholinesterase medication, may be a useful additional treatment in congenital myasthenia.